Answer:
The solution to the given equation is that the value of x is -8.
Explanation:
-4(2x + 3) = 2x + 6 - (8x + 2)
Distribute -4 to (2x + 3).
-8x - 12 = 2x + 6 - (8x + 2)
Since there is a negative sign in front of (8x + 2) then you will turn the terms into negatives.
-8x - 12 = 2x + 6 - 8x - 2
Now, combine like terms on the right side of the equation.
-8x - 12 = -6x + 4
Add -6x on both sides of the equation.
-2x - 12 = 4
Add 12 to both sides of the equation.
-2x = 16
Divide -2 on both sides on the equation.
x = -8
So, the value of x is -8.